2016
DOI: 10.1039/c5ee02912k
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and electrical control of fullerene dimerization determines organic photovoltaic stability

Abstract: Light induced fullerene dimerization is controlled by both the fullerene and polymer morphology of organic solar cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
232
1
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 207 publications
(250 citation statements)
references
References 54 publications
11
232
1
6
Order By: Relevance
“…The burn-in drop mainly concerns V oc and FF (fill factor), and the photocurrent is reported to be only slightly affected. This behavior was also observed in the case of PCDTBT:PC 60 BM44. In our case, the drop in photocurrent is relatively low (6%) and corresponds almost to the burn-in observed in Fig.…”
Section: Resultssupporting
confidence: 86%
“…The burn-in drop mainly concerns V oc and FF (fill factor), and the photocurrent is reported to be only slightly affected. This behavior was also observed in the case of PCDTBT:PC 60 BM44. In our case, the drop in photocurrent is relatively low (6%) and corresponds almost to the burn-in observed in Fig.…”
Section: Resultssupporting
confidence: 86%
“…Heumueller et al recently showed that this dimerization can be strongly inhibited when the fullerene is mixed with certain charge hole-conducting polymers. [66] Our results here could also be explained by this dimerization occurring, introducing electron traps. With n-doping, the much higher electron density in the C 60 would once more fill these traps and make the impact of fullerene dimerization less severe.…”
Section: Doi: 101002/adma201604186supporting
confidence: 51%
“…11,13,14 While photo-induced reactions between PCBM molecules may lead to morphological stability, 15,16 they can also give rise to dimers that act as charge traps and reduce short circuit current ( J sc ) values. 17 PCBM is also difficult to cast as a thin film, resulting in rough surfaces of large aggregates. In some cases, it has been established that the addition of small amounts of nucleating agents may lead to controlled fullerene crystal growth and thus hinder coarsening of the morphology.…”
Section: Introductionmentioning
confidence: 99%
“…Recent works in the literature have demonstrated that the rate of fullerene aggregation is strongly dependent on its diffusivity and miscibility as well as the extent of photo-induced dimerisation between fullerenes within a polymer matrix. 14,16,17,50,51 These properties are heavily influenced by polymer backbone and side-chain structure and the amorphous/ void space fractions of the thin films through which small molecules may more easily traverse. 17,52 Therefore, it should follow that acceptor migration and aggregation within polymers containing distinctly different backbones and side-chains, and featuring differences in crystallinity and glass transition temperatures should exhibit dissimilar behavior with respect to morphological development.…”
mentioning
confidence: 99%
See 1 more Smart Citation